The effect of special exercises to develop the maximum strength and the achievement of the snatch lift for the players of Al-Muqdadiya Club for weightlifting, the advanced category - NafeaKamil, Ihab; AbdulelahSalama, Omar; Abbas Abood, Suha (International Journal of Psychosocial Rehabilitation, 2020)
Sports training aims to raise the level of achievement, and the remarkable achievements in various sports came as a result of using modern training methods and methods based on scientific foundations that enabled athletes to reach the highest level in sports tournaments. , as well as developing the physical qualities of the players, and as the coach of the Muqdadiya Sports Club for weightlifting, a weakness was observed in the achievement of the snatch lift among weightlifters, the category of applicants in Muqdadiya Governorate, due to the weakness in the maximum strength of the muscles as a result of the trainers’ distance and lack of interest in using different exercises from the usual, so the researcher sees from Through his modest and simple experience, he developed special exercises different from the classic training. The exercises prepared by the researcher contributed to developing the maximum strength of weightlifting players, the advanced category in the snatch, in addition to achieving the training mechanism on the curriculum different from the classic exercises in developing the maximum strength of the players.